Estudio comparado de los ingresos y gastos del portafolio de microempresarios de la empresa Negolevel S.A. antes y en estado de excepción por crisis sanitaria - Cofre Carrillo, Mayra Alejandra (2021)
Comparatively studying the income with respect to the expenses of a company, allows us to place ourselves within the categories of surplus or deficit, starting from this premise we can know the performance of the companies. Examining the impact of COVID-19 on the different economies of countries is considered a cutting-edge topic today. In this sense, the present investigation is carried out "Comparative study of the income and expenses of the portfolio of microentrepreneurs of the company Negolevel SA before and in a state of exception due to a health crisis" the different consequences that the pandemic caused in the microentrepreneurs of the portfolio of the NEGOLEVEL SA company belonging to the three sectors of the Ecuadorian economy: primary, secondary and tertiary……….